International guidelines for the in vivo assessment of skin properties in non-clinical settings: Part 2. transepidermal water loss and skin hydration - Plessis, Johan du; Stefaniak, Aleksandr; Eloff, Fritz; John, Swen; Agner, Tove; Chou, Tzu-Chieh; Nixon, Rosemary; Steiner, Markus; Franken, Anja; Kudla, Irena; Holness, Linn (Skin research and technology, 2013)
Background There is an emerging perspective that it is not sufficient to just assess skin exposure to physical and chemical stressors in workplaces, but that it is also important to assess the condition, i.e. skin barrier function of the exposed skin at the time of exposure. The workplace environment, representing a non‐clinical environment, can be highly variable and difficult to control, thereby presenting unique measurement challenges not typically encountered in clinical settings. Methods An expert working group convened a workshop as part of the 5th International Conference on Occupational and Environmental Exposure of Skin to Chemicals (OEESC) to develop basic guidelines and best practices (based on existing clinical guidelines, published data, and own experiences) for the in vivo measurement of transepidermal water loss (TEWL) and skin hydration in non‐clinical settings with specific reference to the workplace as a worst‐case scenario. Results Key elements of these guidelines are: (i) to minimize or recognize, to the extent feasible, the influences of relevant endogenous‐, exogenous‐, environmental‐ and measurement/instrumentation‐related factors; (ii) to measure TEWL with a closed‐chamber type instrument; (iii) report results as a difference or percent change (rather than absolute values); and (iv) accurately report any notable deviations from this guidelines. Conclusion It is anticipated that these guidelines will promote consistent data reporting, which will facilitate inter‐comparison of study results.